Electron Impact Double Ionisation of Lanthenum (La++): Extension of Binary Encounter Approximation to La++ Ion (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper provides extension of the binary encounter approximation calculations. In the case of +ve ions to the case of La++ ion.